Dumézil, Ideology, and the Indo-Europeans - Lincoln, Bruce (Zeitschrift für Religionswissenschaft, 1998)
The author suggests that Dumézil's most important contribution was his insistence on the ideological character of myth, while other aspects of his writings are more problematic. In particular, he questions whether Dumézil's affinity for Charles Maurras and the Action Française led him to constitute diverse data as an idealized »system of three functions.« Going beyond the question of Dumézil per se, and invoking the example of Procopius, Vandalic War 1.2.2-5, he treats the notion of an »Indo-European« people as a discursive construct that attempts to dissolve the diversity of historically attested evidence in an almost mythic narrative of unity and perfection in the most ancient past.